Assessing the Rate of Replication in Economics - Berry, James; Coffman, Lucas C.; Hanley, Douglas; Gihleb, Rania; Wilson, Alistair J. (American Economic Review, 2017)
We assess the rate of replication for empirical papers in the 2010 American Economic Review. Across 70 empirical papers, we find that 29 percent have 1 or more citation that partially replicates the original result. While only a minority of papers has a published replication, a majority (60 percent) have either a replication, robustness test, or an extension. Surveying authors within the literature, we find substantial uncertainty over the number of extant replications.